APAKAH MATERIALISME DAN BUDAYA ORGANISASI BERPENGARUH TERHADAP TERJADINYA KECURANGAN? PERAN RELIGIUSITAS SEBAGAI MODERASI: DO MATERIALISM AND ORGANIZATIONAL CULTURE INFLUENCE THE OCCURRENCE OF FRAUD? THE ROLE OF RELIGIOSITY AS MODERATION - Fadhillah, Muhammad Yafi; Yesi Mutia Basri; Yasni, Hariadi (Universitas Riau, 2024)
Fraud is an unlawful act and deed that commonly occurs in an organization or company. The purpose of this study is to see how the influence of materialism, organizational culture, materialism moderated by religiosity and organizational culture moderated by religiosity on fraud in ASN Pekanbaru City Government. The population in this study was the State Civil Apparatus (ASN) in the Pekanbaru City Government, which was 7164 people. This study uses a quantitative method. The sampling technique used purposive sampling, with the characteristics of ASN who have positions. The data collection technique used a questionnaire by distributing questionnaires via google forms. There were 118 questionnaires analyzed. The results of data analysis using SmartPLS 3.0 showed that materialism had no effect, organizational culture had a negative effect, religiosity strengthened the influence of materialism, religiosity strengthened the influence of organizational culture on the tendency of fraud in ASN Pekanbaru City Government. The results of this study are expected to contribute to the government in efforts to reduce and prevent fraudulent acts, especially in the government sector.